Previous Exercise Training Has a Beneficial Effect on Renal and Cardiovascular Function in a Model of Diabetes - Silva, Kleiton Augusto dos Santos; Luiz, Rafael da Silva; Rampaso, Rodolfo Rosseto; de Abreu, Nayda Parísio; Moreira, Édson Dias; Mostarda, Cristiano Teixeira; De Angelis, Kátia; de Paulo Castro Teixeira, Vicente; Irigoyen, Maria Cláudia; Schor, Nestor (PLOS ONE, 2012)
Exercise training (ET) is an important intervention for chronic diseases such as diabetes mellitus (DM). However, it is not known whether previous exercise training intervention alters the physiological and medical complications of these diseases. We investigated the effects of previous ET on the progression of renal disease and cardiovascular autonomic control in rats with streptozotocin (STZ)-induced DM. Male Wistar rats were divided into five groups. All groups were followed for 15 weeks. Trained control and trained diabetic rats underwent 10 weeks of exercise training, whereas previously trained diabetic rats underwent 14 weeks of exercise training. Renal function, proteinuria, renal sympathetic nerve activity (RSNA) and the echocardiographic parameters autonomic modulation and baroreflex sensitivity (BRS) were evaluated. In the previously trained group, the urinary albumin/creatinine ratio was reduced compared with the sedentary diabetic and trained diabetic groups (p<0.05). Additionally, RSNA was normalized in the trained diabetic and previously trained diabetic animals (p<0.05). The ejection fraction was increased in the previously trained diabetic animals compared with the diabetic and trained diabetic groups (p<0.05), and the myocardial performance index was improved in the previously trained diabetic group compared with the diabetic and trained diabetic groups (p<0.05). In addition, the previously trained rats had improved heart rate variability and BRS in the tachycardic response and bradycardic response in relation to the diabetic group (p<0.05). This study demonstrates that previous ET improves the functional damage that affects DM. Additionally, our findings suggest that the development of renal and cardiac dysfunction can be minimized by 4 weeks of ET before the induction of DM by STZ.